(untitled) (Development Service Industry Management, 2024)
In the current conditions of Russian aggression in Ukraine, the issue of finding directions for the economic recovery of Ukraine and reviving its economic potential is becoming urgent. Active hostilities have led to significant mass movements of citizens who leave their homes in search of safety and protection, which creates a significant burden on the state budget in the form of various forms of financial assistance to internally displaced persons. Therefore, the development of mechanisms for their economic and social integration into the new living conditions in the host territorial communities should be included among the priority tasks at the state level. One of these tools is the development of a set of measures to attract such persons to the development of tourism entrepreneurship, because a significant amount of tourism and recreation resources is concentrated in Ukraine. The purpose of the study is to systematize the international experience of supporting displaced persons through the development of tourism entrepreneurship, as well as to develop recommendations for the development of tools to support internally displaced persons in Ukraine. According to the authors of the study, the conceptual content of the category "tourism potential" refers to hidden opportunities for the development and growth of the tourism industry within a specific region. It includes a specific list of resources, historical sites, infrastructure and services that can be used to attract visitors and stimulate tourism-related activities. Assessing the potential of tourism involves identifying these assets, determining their ability to generate economic benefits, create employment opportunities, enhance cultural exchange and promote sustainable development. Ultimately, realizing the potential of tourism requires effective planning, investment, interaction of central executive authorities with local territorial communities, marketing and management strategies to utilize available resources and transform them into successful tourism experiences and destinations. In general, tourism entrepreneurship can promote social cohesion and integration by bringing together migrants and residents of host territorial communities in joint tourism activities and initiatives, which will give them the opportunity to feel a sense of belonging and recognition, reducing social isolation and promoting economic and social integration.